2013
DOI: 10.1080/07347332.2012.761322
|View full text |Cite
|
Sign up to set email alerts
|

Stress Coping and Changes in Health Behavior Among Cancer Survivors: A Report from the American Cancer Society's Study of Cancer Survivors-II (SCS-II)

Abstract: This study used the transactional model of stress and coping to examine the relationship between cancer survivors' self-reported efforts to manage stress and the adoption of health behaviors across various lifestyle behavior domains. The authors analyzed data of 2,888 cancer survivors from a national, population-based, cross-sectional survey. Cancer survivors who indicated making active efforts to control stress were more likely to make changes in their physical, psychosocial, and preventive health behaviors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
6
20
1
Order By: Relevance
“…Contrary to the results of previous studies (Bishop & Warr, 2003;McLaughlin et al, 2013;Parelkar, Thompson, Kaw, Miner, & Stein, 2013;Roesch et al, 2005;Unger et al, 2013), we found that active coping was associated with more functional limitations and, indirectly, with a lower self-assessed work ability and with not having paid work. Nevertheless, we found associations of active coping with fewer self-reported limitations for ambulation, better cognitive functioning (QLC) and fewer depressive symptoms.…”
Section: The Role Of Coping In Cancer Survivorscontrasting
confidence: 99%
“…Contrary to the results of previous studies (Bishop & Warr, 2003;McLaughlin et al, 2013;Parelkar, Thompson, Kaw, Miner, & Stein, 2013;Roesch et al, 2005;Unger et al, 2013), we found that active coping was associated with more functional limitations and, indirectly, with a lower self-assessed work ability and with not having paid work. Nevertheless, we found associations of active coping with fewer self-reported limitations for ambulation, better cognitive functioning (QLC) and fewer depressive symptoms.…”
Section: The Role Of Coping In Cancer Survivorscontrasting
confidence: 99%
“…Therefore, active strategies for patients to take control of their diet post‐diagnosis are needed. In line with previous evidence (Parelkar et al., ) this paper suggests that interventions should consider strategies to utilise active coping behaviours for patients while educating health professionals on the role of diet in prostate cancer using public health and educational tools. Patient interventions should also take into account cognitive and emotional functioning.…”
Section: Discussionsupporting
confidence: 82%
“…Greater perceived control may mediate this association. Control is related with a greater likelihood of making difficult behavioural changes (Thompson & Schlehofer, ; Thompson & Spacapan, ) like adhering to a healthier diet (Parelkar, Thompson, Kaw, Miner, & Stein, ). Also, patients who perceive health as a matter of chance are less likely to adhere to healthy behaviours (Grotz, Hapke, Lampert, & Baumeister, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it was determined that the perceived social support from family and total perceived social support were associated with effective coping with stress. In the literature, social support was found useful for patients with cancer, and these patients often received support from their families . It was determined that the support received from family members had a positive correlation with well‐being of patients with cancer, and as the support received from family increased, effective coping ways increased .…”
Section: Discussionmentioning
confidence: 99%